High strain rate response of bio-composites using split Hopkinson pressure bar and digital image correlation technique. (2nd January 2019) - Pandya, Tejas S.; Dave, Maharshi J.; Street, Jason; Blake, Cody; Mitchell, Brian
ABSTRACT: In this research, high strain rate response and energy absorption characteristics under dynamic compression loading of five different bio-composites were studied using a compression split Hopkinson pressure bar (SHPB) and DIC (digital image correlation) technique. This study is to map suitability of plant-based materials instead of petroleum-based plastic as a constituent raw material in composites. Bio-composites panels were made from Southern yellow pine (SYP), Corn starch (CS), and Methylene diphenyl diisocyanate (MDI) using a Dieffenbacher hot press. The ability of non-contact DIC analysis served as a valuable tool to measure the strains over a large range of deformation in wood-based bio-composites subjected to high strain rate compressive loading. Among all, Material 2 bio-composite with high manufacturing pressure had highest peak strength, shows that material behaviour at high strain rates is strongly dependent on the manufacturing pressure during fabrication. Presence of corn starch marginally increased the energy absorption capacity.